Odpowiedzi

2010-03-30T21:59:34+02:00
6-(15-x)=5-(1-½x)
6-15+x=5-1+½x
x-½x=5-1-6+15
½x=13 /*2
x=26

4(x+1)=5(x-4)
4x+4=5x-20
4x-5x=-20-4
-x=-24
x=24

5(4x-2)=19⅔x-6
20x-10=19⅔x-6
20x-19⅔x=-6+10
⅓x=4 /*3
x=12
2010-03-30T21:59:39+02:00

6-(15-x)=5-(1-½x)
6-15+x=5-1+½x
x-½x=5-1-6+15
½x=13
x=26


4(x+1)=5(x-4)
4x+4=5x-20
4x-5x=-20-4
-x=-24
x=24



5(4x-2)=19⅔x-6
20x-10=19⅔x-6
20x-19⅔x=-6+10
⅓x=4
x=12
2010-03-30T22:01:36+02:00
6-(15-x)=5-(1-½x)
6-15+x=5-1+½x
-9+x=4+½x /*2
-18+2x=8+x /+18
2x=26+x /-x
x=26

4(x+1)=5(x-4)
4x+4=5x-20 /-4-5x
-x=-24 /:(-1)
x=24

5(4x-2)=19⅔x-6
20x-10=⁵⁹/₃x-6 /*3
60x-30=59x-18 /+30
60x=59x+12 /-59x
x=12